2021
DOI: 10.1039/d0fo02921a
|View full text |Cite
|
Sign up to set email alerts
|

Research progress on the potential delaying skin aging effect and mechanism of tea for oral and external use

Abstract: Tea for oral and external use can anti-UV, antioxidant, anti-inflammatory, inhibit the aging of extracellular matrix, balance intestinal and skin microorganisms, improve mood and sleep, and fundamentally make the skin healthy and natural aging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 188 publications
0
14
1
1
Order By: Relevance
“…17 It inhibits the bitterness and astringency of other foods; improves their flavor; 18 and has notable bioactivities including anti-inflammation, antistress, relaxation, antiapoptosis, hypolipidemia, immunoregulation, and antioxidation. 19–22 Therefore, as a natural biologically active compound, l -theanine is a favorable choice to cope with heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…17 It inhibits the bitterness and astringency of other foods; improves their flavor; 18 and has notable bioactivities including anti-inflammation, antistress, relaxation, antiapoptosis, hypolipidemia, immunoregulation, and antioxidation. 19–22 Therefore, as a natural biologically active compound, l -theanine is a favorable choice to cope with heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Hence, the advancement of sunscreen products to protect against UVB irradiation has drawn widespread attention. 31,32 Here, we found for the first time that ginsenoside Rk1, a rare ginsenoside, is the key active component extracted from ginseng. It substantially diminished skin photoaging in UVB-irradiated BALB/c nude mouse skin and HaCaT keratinocytes by reversing oxidative stress, the inflammatory response, and collagen degradation mediated by the PI3K/AKT/NF-κB signaling pathway.…”
Section: ■ Discussionmentioning
confidence: 79%
“…Acute and long-term exposure of the skin to UVB has been demonstrated to cause irreversible damage to cellular components, have a significant effect on the development of skin aging, and sometimes even bring about skin cancer. , Hence, the advancement of sunscreen products to protect against UVB irradiation has drawn widespread attention. , Here, we found for the first time that ginsenoside Rk1, a rare ginsenoside, is the key active component extracted from ginseng. It substantially diminished skin photoaging in UVB-irradiated BALB/c nude mouse skin and HaCaT keratinocytes by reversing oxidative stress, the inflammatory response, and collagen degradation mediated by the PI3K/AKT/NF-κB signaling pathway.…”
Section: Discussionmentioning
confidence: 80%
“…Tea is one of the three most consumed beverages in the world and is known as the beverage of the twenty-first century, not only because of the long history of tea culture but also because of its nutritional value and health care functions ( 34 , 35 ). Studies have shown that tea contains numerous active ingredients, mainly tea polyphenols, tea pigments, tea polysaccharides, γ-aminobutyric acid, tea saponins, alkaloids, vitamins, pyrroloquinoline quinone, pantothenic acid, minerals, and other ingredients ( 36 , 37 ). Tea polyphenols are the most abundant soluble components in tea, and they are also the most important substances in tea that exert biological effects ( 35 ) that can reduce the incidence of cardiovascular disease, decrease blood lipids, decrease body fat formation, and change the intestinal flora ecology ( 35 , 38 ).…”
Section: Discussionmentioning
confidence: 99%